2005
DOI: 10.1111/j.1360-0443.2005.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in smoking and the role of public policies: results from the SimSmoke tobacco control policy simulation model

Abstract: Among public tobacco control policies, price had the dominant effect on smoking prevalence between 1993 and 2003, because few states implemented other policies to the degree necessary to affect much change. Through continued tax increases, stronger clean air laws, extensive media campaigns and broader cessation treatment programs, there is the potential to have much larger reductions in smoking prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
88
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 24 publications
5
88
2
1
Order By: Relevance
“…The number of lives saved each year is projected to increase as benefits from cessation increase and those who are deterred from smoking initiation reach an age of 35 when smokers have higher mortality risks than non-smokers. Consistent with our earlier models for the United States (Levy et al 2005b) and for Arizona (Levy, Bauer et al forthcoming Unlike a simple trend line prediction, the model also does reasonably well at predicting trends over various sub-periods of time corresponding to policy changes (the price increase and implementation of the media campaign in 1988, the reduction in the media campaign in 1993, the price increase in late 1998). California SimSmoke generally shows a larger drop between 1996 and 1999 and underestimates the drop between 1999 and 2002 relative to the other data sets, but the smoking prevalence estimates from the different data sets show different trends over these sub-periods.…”
Section: Discussionsupporting
confidence: 67%
“…The number of lives saved each year is projected to increase as benefits from cessation increase and those who are deterred from smoking initiation reach an age of 35 when smokers have higher mortality risks than non-smokers. Consistent with our earlier models for the United States (Levy et al 2005b) and for Arizona (Levy, Bauer et al forthcoming Unlike a simple trend line prediction, the model also does reasonably well at predicting trends over various sub-periods of time corresponding to policy changes (the price increase and implementation of the media campaign in 1988, the reduction in the media campaign in 1993, the price increase in late 1998). California SimSmoke generally shows a larger drop between 1996 and 1999 and underestimates the drop between 1999 and 2002 relative to the other data sets, but the smoking prevalence estimates from the different data sets show different trends over these sub-periods.…”
Section: Discussionsupporting
confidence: 67%
“…As we reported, the fit of our predicted model for smoking prevalence in this group is only reasonable. Yet, the data showed that between 2000 and 2006, the proportion of smokers in the middle age group (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in men among the lowest socioeconomic class in our study was 40% in 2000 and 43% in 2006. Secondly, the analysis was restricted to groups I and V. Because of changes in the nature of works and occupation in the late twentieth century, group V is gradually becoming smaller over time i.e.…”
Section: Discussioncontrasting
confidence: 57%
“…Despite the fact that tobacco is addictive, research on the effects of the price of tobacco products on population rates of smoking has repeatedly suggested that there is an inverse relationship between the price and consumption of cigarettes (Frieden et al, 2005;Levy et al, 2005aLevy et al, , b, 2006Niaura and Abrams, 2002). Further of all de-marketing strategies including anti-smoking advertising and legal restrictions on smoking, price increases on cigarettes have been found to bear the strongest relationship to population rates of smoking (Levy et al, 2005b).…”
Section: Introductionmentioning
confidence: 95%